Splatoon. Vol. 1 - Hinodeya, Sankichi; Miyaki, Tetsuichiro; Haun, Jeremy; Hurley, Jason A., 1981-; Hunt, John, 1972- (San Francisco, CA : Viz Media, LLC, 2017)
The Turf Wars have started in Inkopolis, and the team that inks the most ground will be crowned the winner! Goggles and Team Blue are ranked lower than their competitors. But with some teamwork and a touch of creativity, they might just leave their mark on this tournament!
Translated from the Japanese.
5-8
Book reads from right to left in the traditional Japanese format.
5.0
Keywords: Contests -- Comic books, strips, etc -- Fiction; Creative ability -- Comic books, strips, etc -- Fiction; Manga; Squids -- Comic books, strips, etc -- Fiction; Contests -- Juvenile fiction; Graphic novels; Creative ability -- Juvenile fiction; Squids -- Juvenile fiction; Humorous stories; Comics (Graphic works)